2020
DOI: 10.7759/cureus.8789
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Pathogenesis of Immunoglobin A Nephropathy

Abstract: The understanding of the pathogenesis of any disease is the key to effective and specific treatment of the disease. immunoglobulin A (IgA) nephropathy is an autoimmune disease of the kidney. Oxford MEST classification is commonly used to stratify patients according to the severity of the disease. Patients with IgA nephropathy seem to produce anti-GalNAc antibodies against a particularly defective IgA1. This immune complex deposits in the kidneys, leading to a type 3 hypersensitivity reaction which ultimately d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…IgA nephropathy (IgAN), also known as Berger's disease, is divided into two categories: primary and secondary. Primary IgA nephropathy is more common, accounting for about 36.7% to 58.2% of primary glomerular diseases diagnosed by renal pathology in China, and its incidence has been gradually increasing in recent years [1,2]. It can be seen at any age, and patients aged 16-35 years account for about 80% of the total number of patients with the disease [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…IgA nephropathy (IgAN), also known as Berger's disease, is divided into two categories: primary and secondary. Primary IgA nephropathy is more common, accounting for about 36.7% to 58.2% of primary glomerular diseases diagnosed by renal pathology in China, and its incidence has been gradually increasing in recent years [1,2]. It can be seen at any age, and patients aged 16-35 years account for about 80% of the total number of patients with the disease [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, leflunomide was also shown to inhibit the activity of dihydrofolate dehydrogenase and cell cycle-dependent kinases, further preventing the proliferation of T and B lymphocytes and immune responses [ 46 ]. In view of the importance of autoimmunity in the pathogenesis of IgAN, leflunomide could also confer its therapeutic efficacy for IgAN as an immunosuppressant [ 47 ]. In addition, some studies also suggested a possible direct benefit of leflunomide on glomerular disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, with early diagnosis and treatment, most people with IgA nephropathy can live a normal life ( 36 ). The link between a dysregulated gut-associated lymphoid tissue (GALT) and IgAN was hypothesized following the observation of a higher association between IgA nephropathy and celiac disease ( 37 ). However, in people with IgAN, GALT can become dysregulated, leading to the production of abnormal IgA antibodies.…”
Section: Iga Nephropathy and Celiac Diseasementioning
confidence: 99%